Abundances of Tetracycline Resistance Genes and Tetracycline Antibiotics during Anaerobic Digestion of Swine Waste. Issue 1 (1st January 2019) - Couch, Melanie; Agga, Getahun E.; Kasumba, John; Parekh, Rohan R.; Loughrin, John H.; Conte, Eric D.
Abstract : The impact of anaerobic digestion of animal waste on the persistence of antibiotic resistance genes (ARGs) and antibiotics is not widely studied. Two identical, 800‐L digesters seeded with swine slurry were followed up to 100 d in three separate trials. The trials received varying amounts of antibiotic‐free corn ( Zea mays L.) mixed with water to maintain the digestion process. Biogas production, seven tetracycline resistance ( tet ) genes, and three tetracyclines and their transformation products were measured. Biogas production proportionally increased as the feeding loads increased between trials. In Trial 1, log10 tet gene copies showed small but statistically significant ( P < 0.01) increases during digestion. In Trial 2, anaerobic digestion did not have a significant ( P > 0.05) effect except for significant reductions in tet B ( P < 0.0001) and tet G ( P = 0.0335) log10 gene copies. In Trial 3, which received the highest amount of corn mix, log10 copies of the 16S ribosomal RNA and the tet genes significantly ( P < 0.0001) reduced over time during digestion. Up to 36 μg L −1 tetracycline, 112 μg L −1 chlortetracycline, 11.9 mg L −1 isochlortetracycline, and 30 μg L −1 4‐epitetracycline were detected both in the liquid and solid digestates. Results of this study revealed that although anaerobic digestion of swine waste can produce useful biogas, it does not result in complete removal of bacteria, ARGs, and antibiotics regardless of differences in the feeding loads between trials. Further effluent and sludge treatments are required prior to their downstream use in crop production to minimize emergence and environmental dissemination of antimicrobial‐resistant bacteria through animal manure. Core Ideas: Anaerobic digestion did not completely remove resistance genes from swine waste. Tetracycline antibiotics were detected from 30 μg L −1 to 11.9 mg L −1 . Further waste treatments are required to reduce the spread of resistance genes.